Pelatihan untuk Penerapan Teknologi Pengolahan Minuman Gel Lidah Buaya di Ghra Sambiroto, Nanggulan, Kulon Progo, DIY - Chatarina Wariyah; Agus Slamet; Yanri Wijayanti Subronto (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Flavonoids are antioxidant compounds found in aloe vera. Aloe vera gel drink processing has been carried out by Aloe Ku or the aloe vera farmer association in Ghra Sambiroto, Nanggulan, Kulon Progo, DIY. The product is processed through cutting and heating stages so that the gel's antioxidant properties are reduced. The observation results showed that the aloe vera gel drink in Ghra Sambiroto had less than optimal antioxidant activity. This activity aims to improve the processing of aloe vera gel drinks so that their antioxidant activity is high. Training was carried out through counseling, practice, mentoring, and evaluation of knowledge and abilities. The results showed increased skills in processing aloe vera gel drinks based on the Pearson correlation between 0.7302–0.9467. Aloe vera gel drinks have the characteristics of total sugar of 13.35%, gel hardness with a force that can be held at 96.25 g/cm2 and deformation of 2.81 mm, and the ability to capture free radicals (Radical Scavenging Activity, RSA) 6.72%.